Solid–liquid phase change modelling of metallic sodium for application in solar thermal power plants. (September 2015) - Boerema, Nicholas; Taylor, Robert A.; Morrison, Graham; Rosengarten, Gary
Highlights: We address the issue of solidification of metallic sodium in concentrated solar thermal power plants. A solid–liquid phase change model has been developed using Fluent for metallic sodium. Validation of the model has been performed through physical experiments. The model was shown to be reliable and robust and had good correlation to the physical experiments. Examples of the beneficial use of this method in solar thermal systems are given. Abstract: Liquid sodium presents a possibility for improved economics in concentrating solar thermal power plants. As the melting temperature of metallic sodium is above ambient temperatures (97.8 °C), melting of sodium in components will at times be necessary. A solid–liquid phase change model has been developed using Fluent for metallic sodium. The model was validated using a physical experiment in which metallic sodium was heated and cooled in a cylinder across the phase change temperature. The movement of the phase change front from the simulation was then compared to that of the physical experiment. The model was shown to be reliable and robust and had good correlation to the physical experiments. Examples of the beneficial use of this method in solar thermal systems are given, consisting of thermal storage systems, stem freeze seals and melting of the heat transfer fluid in receiver tubing.